Effect of a non-peptide angiotensin receptor antagonist on water intake caused by centrally administered carbachol in the rat - Reis, L. C.; Saad, W. A.; Camargo, LAA; Renzi, Antonio [UNESP]; Menani, José Vanderlei [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 1996)
Angiotensin II (ANG II) administered centrally produces drinking by acting on subtype 1 ANG II (AT1) receptors, Carbachol, a cholinergic receptor agonist, also induces drinking behavior by a central action. In the present study we determined whether the response to carbachol also involves AT1 receptors. Male Holtzman rats (250-300 g) with stainless steel cannula implanted into the lateral ventricle (LV) were used. Water intake after injection of 0.15 M NaCl (1.0 mu l) into the LV was 0.2 +/- 0.01 ml/h (N = 8). The AT1 receptor antagonist DUP-753 (50 nmol/mu l) injected into the LV reduced water intake induced by ANG II (10 nmol/mu l) from 9.2 +/- 1.4 to 0.4 +/- 0.1 ml/h (N = 8), and water intake induced by carbachol (2 nmol/mu l) from 9.8 +/- 1.4 ml/h to 3.7 +/- 0.8 ml/h (N = 8), These results suggest that AT1 receptors play a role in the drinking behavior observed after central cholinergic stimulation in rats.
Keywords: water intake; angiotensin 11; carbachol; DUP-753; angiotensin receptor antagonist; AT1 receptor